Critical Medication Shortages: Effective Strategies to Maintain Continuous Medication Availability for Emergency Medical Services. (3rd March 2020) - Whitfield, Denise; Bosson, Nichole; Habrat, Dorothy; Telmos, John; Watson, Gary; Eckstein, Marc; Kazan, Clayton; Gausche-Hill, Marianne
Abstract: Objective: Critical shortages of generic injectable medications are an ongoing challenge for Emergency Medical Services (EMS) systems. Mitigation strategies have been proposed to address the issue, but a limited amount of data exists quantifying the scope of the problem or describing strategies being used to ensure access to essential medications for prehospital care. In this study, we sought to quantify specific medication shortages and to determine the most frequently employed mitigation strategies to maintain medication availability in a large, regional EMS system. Methods: A survey was distributed to the 30 public advanced life support (ALS) provider agencies in Los Angeles County (LAC) to assess the prevalence of specific medication shortages and types of shortage mitigation strategies implemented. Survey responses were reviewed and presented using descriptive statistics. Results: Survey responses were received from 29 of 30 (97%) provider agencies. All but one of the responding agencies reported being impacted by medication shortages. Strategies to maintain the supply of medications included use of alternative vendors 20/28 (71%), rotating medications from low to high volume units (54%), utilizing expired medication FDA-approved extensions (50%), substituting medications (43%), borrowing medications from the LAC EMS Agency (39%) or other EMS provider agencies (32%), utilizing expired medications with medical director approval (29%), diluting medications to obtain desired concentration (18%), reducing minimum periodic automatic replacement (PAR) levels (14%), and using alternate medication concentrations/formulations (14%). The medications most frequently reported to have shortages included epinephrine (0.1 mg/mL), morphine, dextrose 10%, and normal saline. None of the provider agencies self-reported adverse events due to the shortages. Conclusions: Critical medication shortages remain a problem for many EMS systems. EMS medical directors need to implement multiple mitigation strategies to maintain supply of critical medications for prehospital patient care.